International Policy Coordination and Simple Monetary Policy Rules - Wolfram Berger (Swiss Journal of Economics and Statistics, 2010)
This paper studies monetary policy in an optimizing two-country model. We suppose a two-step production process that is associated with vertical trade. Prices of final consumption goods are sticky and pass-through can be incomplete. Monetary authorities should respond to both home and foreign shocks in this set-up. Which simple, i.e. non-optimal, targeting rule best supports the welfare maximizing policy hinges critically on the degree of the cross-country interdependence in production and the relative importance of productivity and cost-push shocks. We argue that the relative volatility of productivity and cost-push shocks determines whether the monetary authority should follow a price targeting rule whereas the degree of vertical integration determines which simple price targeting rule (producer or consumer price index targeting) is best.
Keywords: F41; F42; E52; E58; 330; policy coordination; policy rule; consumer price targeting; producer price targeting; monetary targeting